Unraveling the role of metacognitive processes in generalized anxiety disorder: a moderated mediation model - Styba-Nelson, Kevin (My University, 2025)
Recent research has suggested that worry related metacognitions may play a moderating role in the relationships that anxiety-related dysfunctional beliefs have with chronic worry and generalized anxiety disorder (GAD). The present studies sought to investigate this possible moderating relationship in an undergraduate sample and a community sample. The first study included an undergraduate sample of 573, and investigated if negative metacognitive beliefs (i.e., that worry is dangerous or uncontrollable; NBW) or positive metacognitive beliefs (i.e., that worry is useful or beneficial; PBW) moderated the relationship that anxiety sensitivity has to chronic worry and the symptoms of GAD. The second study included a community sample of 627, and expanded upon the first study by investigating how neuroticism may contribute to chronic worry and GAD symptoms through anxiety sensitivity and intolerance of uncertainty. It was also investigated if NBW and PBW moderated these mediated pathways from neuroticism to GAD. Results from both studies generally concluded that NBW and PBW did not have a moderating role on these relationships. Despite this, NBW still appears to have a significant relationship with GAD. Future research may wish to investigate the direct or mediational effects of metacognitive beliefs on GAD, rather than investigating them as moderators.
Presented June 12-14, 2025, at the Canadian Psychological Association’s 86th National Annual Convention held at the St. John’s Conference Centre in St. John’s, Newfoundland.
Keywords: metacognitions; anxiety-related dysfunctional beliefs; generalized anxiety disorder (GAD); chronic worry; anxiety sensitivity